Dexmedetomidine modulates gut microbiota and improves long-term survival in sepsis patients with pre-existing malignancies: a propensity-matched analysis - Zeng, Yisen; Wu, Huiling; Zhang, Huaijian; Ye, Xiuhong; Chen, Ling; Ye, Yibin (Frontiers in Microbiology, 2025)
BackgroundThe interplay between sedative agents and the gut microbiome may influence long-term outcomes in sepsis, but data are scarce. This study compared the effects of dexmedetomidine vs. propofol sedation on long-term survival in mechanically ventilated sepsis adults, with an exploratory focus on the gut microbiome and pre-existing malignancies.MethodsIn this multicenter, retrospective cohort study, 1,295 mechanically ventilated adults with sepsis (2013–2020) were analyzed. Propensity score matching (1:1) balanced 27 baseline covariates, producing 177 matched pairs. Primary outcomes were 30-day, 90-day, and 5-year mortality. Secondary outcomes included delirium/coma-free days, cardiovascular safety, and 6-month functional status. Subgroup analyses assessed pre-existing malignancies and high antibiotic exposure (≥7 days before enrollment) as proxies for microbiome disruption. Gut microbiota composition was characterized via 16S rRNA sequencing in a pre-specified subcohort (n = 89).ResultsAfter matching, dexmedetomidine was associated with significantly lower 5-year mortality (34.5% vs. 45.2%; HR 0.64, 95% CI 0.52–0.79; p = 0.039). Survival curves progressively diverged beyond 180 days. No differences were observed in short-term neurological outcomes or cardiovascular safety. Subgroup analyses showed enhanced survival benefits with dexmedetomidine in patients aged >65, females, those with pulmonary-source sepsis, SOFA >10, baseline delirium, pre-existing malignancies (OR 2.10, 95% CI 1.15–3.85; p = 0.015), and high antibiotic exposure as a proxy for gut dysbiosis (OR 1.95, 95% CI 1.08–3.52; p = 0.028). Exploratory 16S rRNA analysis in a subset (n = 89) revealed that dexmedetomidine was associated with enriched beneficial genera such as Faecalibacterium and Bifidobacterium, while propofol correlated with increased Enterococcusand Escherichia/Shigella.ConclusionsDexmedetomidine sedation is associated with a significant 5-year survival benefit in mechanically ventilated sepsis patients, particularly among those with malignancies or factors predisposing to gut dysbiosis. The observed modulation of the gut microbiome toward a more symbiotic state provides a plausible mechanistic insight into these clinical findings, highlighting a potential role for microbiota-centric strategies in critical care.